Guidance from Teacher Centers: A possible model for lines of action - Ortiz Cruz, Manuel; Díaz Rey, Clara E.; Hernández De La Cruz, José María; Medina Trujillo, Francisca; González Pérez, Estefanía; Montesino Cruz, Soraya; De La Cruz Jacinto Del Castillo, Hilario (Profesorado, Revista de Currículum y Formación del Profesorado, 2008)
In this report about their working experience, the staff from CEP Valle de La Orotava (Tenerife) present the ways they understand the tasks related to educational advising at schools. This center covers a large area from four different towns in the northern part of the island (about 50 Primary and Secondary schools).They try to show the main criteria that rule these advising tasks especially referring at the responses to the requirements from the schools. One of the most important among these criteria is to take the opportunities to create the common spaces to educational improvement at the own schools throughout the formal or informal conditions and keeping as the first aim the whole staff of each school as the reference in this process. However there will be found other references to other examples of more specific advising and about how create improvement areas out of the school organization and the ways they have created to make them possible. Finally a review of the opportunities and obstacles found through this process is offered, attending not only at the characteristics of the schools but also other special conditions, especially those referred to educational administration.